Experimental study on the flow behaviour of water-sand mixtures in fractured rock specimens - Zhang, Boyang; He, Qingyuan; Lin, Zhibin; Li, Zhenhua (International journal of mining science and technology, 2021)
The study of flow behaviour of water-sand mixtures in fractured rocks is of great necessity to understand the producing mechanism and prevention of water inrush and sand gushing accidents. A self-developed seepage test system is used in this paper to conduct laboratory experiments in order to study the influence of the particle size distribution, the void ratio, and the initial mass of Aeolian sand on the flow behavior. It is concluded that the water flow velocity is insensitive to the initial mass of the Aeolian sand but increases with the power exponent in the Talbot formula and the specimen height. The outflow of the Aeolian sand increases with the power exponent in the Talbot formula, the specimen height, and the initial mass of the Aeolian sand. Besides, the outflow of the Aeolian sand changes exponentially with the water flow velocity. Finally, it is found that the fractured specimen has a maximum sand filtration capacity beyond which the outflow of the Aeolian sand significantly increases with the initial mass of the Aeolian sand.